Efficiency of public expenditure in higher education at Universidad Surcolombiana, 2016-2020 - Piedrahita Guerrero, José Manuel; Artunduaga González, María Orlinda (Cuadernos de Administración, 2024)
This research article presents an analysis of the efficiency of public expenditure in higher education at Universidad Surcolombiana during the period 2016-2020. The study was conducted through an analysis of management indicators applied by the higher education institution, using an efficiency measurement scale based on the appropriated and executed resources from the general budget. These resources are allocated between operating expenses and investment expenses, with the latter directed towards covering projects, programs, and policies within each of the subsystems (Training, Research, Social Projection, University Welfare, and Administration) included in the Plan de Desarrollo Institutional 2015-2024. Furthermore, the operations werecompared with management indicator formulas developed, for both national allocation sources and the university’s own revenue sources, as mechanisms to achieve fiscal balance in investments while fulfilling the institutional mission. Subsequently, a quantitative approach wasadopted, using a deductive analytical and descriptive method appropriate for this type of study. Document review techniques and central tendency measurement techniques, with the aid of Excel, were employed for the respective operational analyses. Finally, the study concluded that the analysis developed on the efficiency indicator of public expenditure in higher education at Universidad Surcolombiana during the period 2016-2020 achieved positive efficiency due to the good balance of its public finances, the growth of installed capacity, the acquisition of laboratories, the increase in intellectual production by faculty and students, and the strengthening of university welfare.